Axial Mode Helix Antenna to Amplify 4G LTE Signal in Rural Area: english - Nasrul; Septima, Uzma; Andrian, Kelvin (Brilliance: Research of Artificial Intelligence, 2023)
Rural areas that may still be difficult to get 4G signals are caused by the diversetopography of the region and uneven landscapes, especially in mountainous areaswhich result in weakness in signal reception in the area. To get 4G signal coveragein this area, it is necessary to have a repeater in the form of an antenna thatfunctions as a signal booster in the area. In this study, a helix antenna consistingof ten windings at the uplink (1710-1785 Mhz) and downlink (1805-1880 Mhz)4G LTE frequencies was designed. It is hoped that this antenna can produce highergain and a more focused beam, with the aim of strengthening 4G signals in ruralareas. The antenna design was tested through the use of CST Studio Suitesoftware. The antenna design has been simulated using CST Studio Suitesoftware. After optimizing the simulation results, a return loss of -14 dB, VSWRof 1.49, a gain of 12.47 dBi, and HPBW of 500 were obtained. From themeasurement results obtained, the helix antenna with ten turns shows goodperformance at a frequency of 1880 Mhz with a return loss of -17.75 dB, VSWRof 1.32, gain of 12.15 dBi, HPBW of 440, and unidirectional polarization.